Redesigning Achilles: 'Recycling' the Epic Cycle in Ovid, Metamorphoses 12.1-13.622 (Unteruschungen der Literatur und Geschichte 89). - Sophia Papaioannou (De Gruyter, 2007)
The book is a detailed study on the structure and the topics of Ovid’s compedium of the Trojan Saga in Metamorphoses 12.1-13.622, the section also referred to as the “Little Iliad”. It explores the motives and the objectives behind the selected narrative moments from the Epic Cycle that found their way into the Ovidian version of the Trojan War. By thoroughly mastering and inspiringly refashioning a vast amount of literary material, Ovid generates a systematic reconstruction of the archetypal hero, Achilles. Thus, he projects himself as a worthy successor of Homer in the epic tradition, a master epicist, and a par to his great Latin predecessor, Vergil.